Clustering Analysis of the Departments of Medical Faculty Hospitals Based on Some Variables: Adnan Menderes University - Sebetci, zel; Aksu, Gökhan (International Journal of Computer Sciences and Engineering, 2025)
The objective of this study is to cluster 40 different departments at the Adnan Menderes University Hospital according to some variables. The data used in the study was obtained from the 2014 statistics of the Adnan Menderes University. Among the hierarchical clustering approaches, complete link method was used as the study attempted to determine the way of merging or partitioning of clusters. The study determined that all independent variables had a significant effect in clustering as the result of the ANOVA test which was done for clustering purpose. Chi-square means and discriminant analysis method was used in order to provide evidence on the validity of the cluster results obtained in the analysis. The results of the study were discussed in two stages. The first stage included the analysis of all 40 units while variables of relevant expense, package loss and SGK deduction were evaluated. The second stage included the analysis of 37 units while the variables of expense, lecturer, assistant, nurse, number of personnel, number of polyclinic rooms, polyclinic area, number of service beds and service area were evaluated. Upon the analysis in the first stage, it was determined the units were gathered under 5 clusters. The analysis showed that both the orthopaedics and oncology units were a cluster on their own while the units of hematology and brain surgery were included in the same cluster. The fourth clusters consist of the units of Cardiovascular Surgery, General Surgery, Emergency and Cardiology while the fifth cluster consists of the all other units. As a result of the analysis in the second stage, it was observed that the number of clusters and units within clusters didn’t vary. In order to determine the validity of the results of the study, it was determined that the number of clusters obtained by calculating Wilk’s lambda coefficient was the same with the number of clusters determined by the complete link method.